Role of Color Doppler Ultrasound to Evaluate the Lower Limb Deep Venous Thrombosis in Diabetic Patients : Color Doppler Ultrasound for Lower Limb Deep Venous Thrombosis - Raza, Muhammad Ahmad; Rauf, Abdul; Khan, Bushra Akmal; Alam, Muhammad Asad; Altuf, Laamia; Alloudin, Aftab; Fatima, Saman (Pakistan Journal of Health Sciences, 2024)
Diabetes mellitus is one of the main risk factors for peripheral arterial disease (PAD), and its occurrence is on the rise. In patients with deep vein stenosis, it is quite prevalent. Deep vein thrombosis is a serious health issue in the United States that impacts more than 2.5 million individuals each year. We searched a variety of search engines and databases, including Google Scholar, PubMed, and NCBI, for papers pertaining to our subject. Data on the assessment of lower limb DVT in diabetic patients were extracted from just 20 articles. The current study examined the assessment of DVT in the lower leg. Individuals with diabetes experience different rates of deep vein thrombosis. The result is not statistically significant, though. The anatomic location of the thrombus indicated that patients with diabetes had a higher likelihood of involvement of the popliteal vein, femoral vein, and common femoral vein compared to non-diabetics.